2012
DOI: 10.1007/s10310-011-0302-5
|View full text |Cite
|
Sign up to set email alerts
|

Virulence of Raffaelea quercivora isolates inoculated into Quercus serrata logs and Q. crispula saplings

Abstract: This study was conducted to compare the virulences of various isolates of Raffaelea quercivora-a fungus that causes Japanese oak wilt disease-towards Japanese oak trees. Five isolates were collected from a wide range of Japan and inoculated into Quercus serrata logs and Q. crispula saplings. The tangential length of the discolored sapwood in the Q. serrata logs differed significantly among the isolates. The trend in isolate virulence was similar for the Q. serrata logs and the Q. crispula saplings. This is the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…These results suggest that the effect of inoculation with RA67 on susceptible Q. crispula trees was primarily a consequence of wounding rather than of fungal virulence. Previously, the virulence of R. quercivora to host trees differed among isolates based on the extent of discoloration (Kusumoto et al 2012(Kusumoto et al , 2014(Kusumoto et al , 2015. However, the non-conductive sapwood appears to form earlier than the discoloration (Murata et al 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggest that the effect of inoculation with RA67 on susceptible Q. crispula trees was primarily a consequence of wounding rather than of fungal virulence. Previously, the virulence of R. quercivora to host trees differed among isolates based on the extent of discoloration (Kusumoto et al 2012(Kusumoto et al , 2014(Kusumoto et al , 2015. However, the non-conductive sapwood appears to form earlier than the discoloration (Murata et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the pathogenicity of R. quercivora to Q. crispula and Q. serrata was demonstrated by death of the trees after multiple-inoculation tests Murata et al 2005). Moreover, the fungal virulence against Japanese fagaceous species, including Q. crispula, appears to differ among the isolates collected from Japan (Kusumoto et al 2012) and other Asian countries (Kusumoto et al 2014(Kusumoto et al , 2015 based on comparisons of the widths of discoloured tissue after single-inoculation tests with R. quercivora. However, no studies have evaluated the virulence of the fungus in terms of the wilting mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…These differences in discoloration may relate to the lower mortality levels of evergreen oaks in the field, because most R. quercivora isolates used in our previous studies were categorized as having low virulence (16,17). The sapwood discoloration widths of these species were comparatively smaller than the deciduous ring-porous Quercus spp.…”
Section: Discussionmentioning
confidence: 86%
“…However, our understanding about tree-fungus interactions remains limited compared with tree-beetle interactions. Furthermore, Kusumoto et al (16,17) collected fungal isolates from Japan and other Asian countries and showed that the most virulent isolate caused twice as much discoloration in Q. serrata logs than the least virulent isolate. In addition, the authors suggested that the xylem vessel arrangement in fagaceous trees (i.e., ring-, radial-, and diffuse-porous wood) is associated with differences in the tangential spread of sapwood discoloration among host species.…”
mentioning
confidence: 99%
“…Phytophthora cinnamomi (sudden oak death) (Brasier, 1996;Juzwik , 2011), Raffaelea quercivora (Kusumoto , 2012;Kubono Ito, 2002;Murata , 2005;2007 (Kim, 2009;Korea Forest Research Institute, 2010). (Platypus koryoensis) Raffaelea sp.…”
Section: Ceratocystis Fagacearum (Oak Wilt)mentioning
confidence: 99%